2019
DOI: 10.1002/cpt.1648
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Informed Dose Selection for Xentuzumab, a Dual Insulin‐Like Growth Factor‐I/II—Neutralizing Antibody

Abstract: Over the past decade, the insulin‐like growth factor (IGF)‐signaling pathway has gained substantial interest as potential therapeutic target in oncology. Xentuzumab, a humanized IgG1 monoclonal antibody, binds to IGF‐I and IGF‐II thereby inhibiting the downstream signaling essential for survival and tumor growth. This pathway is further regulated by circulating IGF binding proteins (IGFBPs). In this work, a mechanistic model characterizing the dynamics and interactions of IGFs, IGFBPs, and Xentuzumab has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Simulations indicated a high neutralisation of free IGF-1 and IGF-2 over time (by at least 91% and 64%, respectively; steady state versus baseline) at a xentuzumab dose of 1000 mg/week. 12 Xentuzumab showed preliminary anti-tumour activity in pre-treated patients with advanced solid tumours, with two PRs observed at doses close to the RBD (once weekly dosing) and durable SD (≥24 weeks) reported in eight patients. These findings are consistent with two phase 1 studies of dusigitumab, which reported SD in Caucasian (US) and Asian (Japanese) patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Simulations indicated a high neutralisation of free IGF-1 and IGF-2 over time (by at least 91% and 64%, respectively; steady state versus baseline) at a xentuzumab dose of 1000 mg/week. 12 Xentuzumab showed preliminary anti-tumour activity in pre-treated patients with advanced solid tumours, with two PRs observed at doses close to the RBD (once weekly dosing) and durable SD (≥24 weeks) reported in eight patients. These findings are consistent with two phase 1 studies of dusigitumab, which reported SD in Caucasian (US) and Asian (Japanese) patients.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the effect of xentuzumab on free IGF-1 and IGF-2 was assessed in a separate mechanistic PK-PD modelling study describing the dynamics and interactions of IGF-1, IGF-2, and IGFBPs in the absence and presence of xentuzumab. 12 This quantitative framework, developed by combining published in vitro and in vivo information with clinical data from the xentuzumab phase 1 studies, enabled prediction of the concentrations of free IGF-1 and IGF-2. Simulations indicated a high neutralisation of free IGF-1 and IGF-2 over time (by at least 91% and 64%, respectively; steady state versus baseline) at a xentuzumab dose of 1000 mg/week.…”
Section: Discussionmentioning
confidence: 99%
“…Even the strategy of a double block of the IGF1R and the IR would have the same limits (and counter-effects) as shown by the clinical trials of linsitinib [99][100][101][102][103], a small molecule inhibiting both RTK receptors. This led to a recent approach conveyed in the development of xentuzumab and disigitumab (double anti-IGF1/IGF2 MAbs), targeting the known IGF ligands rather than their RTKs [104][105][106], currently in phase I testing. Although this approach (that of targeting the IGF ligands rather than their RTKs) may gain more leverage in phase II trials, the risk at phase III remains, since the growth-related, trophic, and protective effects of IGF-I on muscle tissue, bone, and other organs' cellular components (such as the physiological stem cell compartments) may induce systemic effects opposite to those intended (especially in pediatric patients).…”
Section: Learning From the Igf System Targeting In Cancer: Not All LImentioning
confidence: 99%
“…6,12 Our findings are consistent with a mechanistic PK-PD modeling study that suggested high neutralization of free IGF-1 and IGF-2 by at least 90% and 64%, respectively, for the xentuzumab 1000 mg/wk dose (at steady state vs baseline). 13 However, in the previous phase 1 trials, xentuzumab was associated with an increase in total IGF-1 (reaching a plateau at doses of ≥1050 mg/wk), but had no clear effect on total IGF-2 levels. 6 It was suggested that this could be due to a lower binding affinity of xentuzumab to IGF-2 vs IGF-1 and differences in regulation of synthesis of IGF-1 vs IGF-2 (IGF-2 is not affected by the negative feedback mechanism).…”
Section: Discussionmentioning
confidence: 92%